2017
DOI: 10.1186/s12913-016-1955-8
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing the dynamics of workplace stress: a systems-based study of nursing aides

Abstract: BackgroundWorkplace stress is a complex phenomenon that may often be dynamic and evolving over time. Traditional linear modeling does not allow representation of recursive feedback loops among the implicated factors. The objective of this study was to develop a multidimensional system dynamics model (SDM) of workplace stress among nursing aides and conduct simulations to illustrate how changes in psychosocial perceptions and workplace factors might influence workplace stress over time.MethodsEight key informan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 42 publications
2
36
0
1
Order By: Relevance
“…Like in the earlier studies (Jetha et al 2017), poor opportunities to affect working pace increased the mental workload. Work remained mentally burdensome even though the associated variables became better in the final measurement.…”
Section: Discussionsupporting
confidence: 58%
“…Like in the earlier studies (Jetha et al 2017), poor opportunities to affect working pace increased the mental workload. Work remained mentally burdensome even though the associated variables became better in the final measurement.…”
Section: Discussionsupporting
confidence: 58%
“…For nurses in Ontario, Canada research showed that as the importance of income for their family’s well-being increased so did their stress level [39]. The work characteristic of workload is shown to be associated with the work stress of health care workers [10, 20, 2729, 31, 36, 38, 40, 41] and this factor is included as a control variable in our study.
Fig. 1The conceptual model of organizational practices associated with PSWs life and work stress
…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 provides an overview of the key psychological and physiological consequences of stress on employees. Workplace stress negatively affects productivity, level of satisfaction, motivation, absenteeism, and employee fluctuation (Mequilibrium, 2013;Balkan and Serin, 2014;Jetha, Kernan and Kurowski, 2017). Stressed employees have less confidence, poor communication intensity with other employees in the organization, and poor client relationships (Karunanithy and Ponnampalam, 2013;Stickle and Scott, 2016).…”
Section: The Analysis Of Key Negative Effects Of Workplace Stressmentioning
confidence: 99%